Analisis Dampak Perubahan Alih Fungsi Lahan terhadap Pembangunan Rumah Sakit Vertikal di Kelurahan Kota Baru Distrik Abepura - Gabriel Ananda Sinurat; Deasy Widyastomo; Lazarus Ramandey (Venus: Jurnal Publikasi Rumpun Ilmu Teknik, 2025)
Land use conversion for vertical hospital development in urban areas represents a strategic response to increasing healthcare demands, particularly in regions with limited land availability. This study aims to analyze the impacts of land use conversion on vertical hospital development in Kelurahan Kota Baru, Abepura District, Jayapura City. The research employs qualitative descriptive methods with spatial analysis and field observations from 2015-2025. Results show significant land conversion from 3.16 hectares (2015) to 0.19 hectares (2025), with wetland areas (58.31%) being the most affected. The study reveals positive impacts including improved healthcare access and local economic growth, alongside negative impacts such as reduced green open spaces and environmental pressure. The findings contribute to sustainable urban planning strategies for healthcare infrastructure development in Papua.